Variações florais e heterostilia em Palicourea rigida (Rubiaceae) nos cerrados do Brasil Central - Machado, Adriana de Oliveira (2007)
The distyly is a floral polymorphism controlled genetically, where the populations present individuals with pin flowers, that possess long styles and short stamens, and individuals with thrum flowers, that possess short styles and long stamens. Their populations tend to be isoplethyc and anomalies in the distribution of pin and thrum flowers in the populations have usually been associated with the habitat fragmentation and environmental disturbances. Besides morphological characteristics of styles/stigmas anthers/pollen grains, these flowers can also present secondary differences in their morphology. Heterostylous plants usually possess a self-incompatibility system, where fruit-set occurs only after cross pollination between morphs (legitimate cross pollination). Palicourea rigida is a typically distylous species of the Rubiaceae, a family that contains the largest number of distylous species. The species is widely distributed in the Brazilian Cerrados and it is pollinated by hummingbirds. The objective of the present work was to study different populations from P. rigida comparing the distribution of pin vs. thrum individuals and other characteristics associated to heterostyly in order to verify if there were asymmetries between floral morphs and differences among areas that could be associated to environmental conditions or recent changes. The work was carried out in the Parque Estadual da Serra Caldas Novas - PESCAN (GO) and in RPPN of the Clube Caça e Pesca Itororó de Uberlândia - CCPIU (MG) where populations of P. rigida were studied in 2005 and 2006. Density, height and pin/thrum ratio were assessed for flowering individuals in both areas. Flower morphs were investigated for differences in floral morphology, nectar production, reproductive success and site of self incompatibility reactions. In spite of differences in density and individuals height, both populations were isoplethyc, with ratio between floral morphs not significantly different from 1:1. The populations were different probably due to their conservation histories, but such differences do not seem to have affected other characteristics associated to distyly. The anisoplethy was observed for populations of the species in Brasília and for other species of Palicourea. Besides the reciprocal herkogamy, with differences marked between pin/thrum styles and stamens, there were differences in the size of the anthers, stigmas and corolla that were larger in thrum flowers. The nectar production varied in volume and concentration in the two populations, but there was not a pattern that could be associated to each one of the floral morphs. There were no differences in reproductive success, which were high for the two morphs and for both populations, in spite of the species to be remarkably self-incompatible. There were differences in the site of incompatibility barriers between floral morphs that corroborated previous observations for the species and for many other species of Rubiaceae. The incompatibility reaction was more marked and interrupted pollen tube growth in the stigma of thrum flowers, while it was more variable and occurred along the style in pin flowers. All the pistils of flowers collected from both floral morphs in the study areas showed a profusion of pollen grains and pollen tubes, which indicates high pollination efficiency. The main floral visitor and pollinator, in both studied areas, was the hummingbird Eupetomena macroura. The high fruit-set indicates that the pollinators transported enough compatible pollen grains between floral morphs, although they commonly presented territorial behavior. The reproductive success was considered high, specially when compared with other self-incompatible species of the Cerrado.